Implementation of Village Fund Management Policy on Community Empowerment in Cokrodiningratan Village, Yogyakarta City - Muhammad Rizky Syah Tio; Hanantyo Sri Nugroho (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
The urban village Fund is channeled to the subdistrict and delegated to the urban village for the urban village's local infrastructure and community empowerment sector. The object of this research was carried out in the Cokrodiningratan urban village, Yogyakarta City using descriptive qualitative methods. The results of the research on the implementation of the policy on managing funds from Permendagri number 130 of 2018 in Cokrodiningratan Village in 2019 were generally good, in managing urban village funds the government of Cokrodinigratan and community institutions could provide public understanding to adjust to the budget ceiling following regulations, needs, and regional potential. In the community empowerment sector, the supporting and inhibiting factors are from the target group of policies and urban village funds which causes the outcomes of programs and policies to be not optimal.